Idiopathic Giant Cell Myocarditis: A Report of 2 Cases - Kavatkar, Anita Neelkanth; Pathan, Almas Iqbal; Puranik, Shaila Chandrakant (Annals of Pathology and Laboratory Medicine, 2018)
Two cases of idiopathic giant cell myocarditis are reported for their rarity .The first case was of a 47 years old male brought to hospital with a history of uneasiness and sudden death. The second case was of a 55 years old male. Gross examination of heart showed whitish fibrotic areas. Microscopy of the heart in both cases revealed large confluent areas of myocyte necrosis along with plenty of giant cells and lymphocytes and occasional eosinophils. Ziehl Neelsen (ZN ) and periodic acid Schiff (PAS) stains were negative. There were no asteroid bodies or Schumann bodies in the giant cells.